Soluble urokinase plasminogen activator receptor (suPAR) in acute care: a strong marker of disease presence and severity, readmission and mortality. A retrospective cohort study. Issue 11 (2nd September 2016) - Rasmussen, Line Jee Hartmann; Ladelund, Steen; Haupt, Thomas Huneck; Ellekilde, Gertrude; Poulsen, Jørgen Hjelm; Iversen, Kasper; Eugen-Olsen, Jesper; Andersen, Ove
Abstract : Objective: Soluble urokinase plasminogen activator receptor (suPAR) is an inflammatory biomarker associated with presence and progression of disease and with increased risk of mortality. We aimed to evaluate the unspecific biomarker suPAR as a prognostic marker in patients admitted to acute care. Methods: This registry-based retrospective cohort study included 4343 consecutively admitted patients from the Acute Medical Unit at a large Danish university hospital. Time to readmission and death were analysed by multiple Cox regression. Results were reported as HRs for 30-day and 90-day follow-up. Results: During 30-day follow-up, 782 patients (18.0%) were readmitted and 224 patients (5.2%) died. Comparing 30-day readmission and mortality between patients in the highest and lowest suPAR quartiles yielded HRs of 2.11 (95% CI 1.70 to 2.62) and 4.11 (95% CI 2.46 to 6.85), respectively, when adjusting for age, sex, Charlson score and C reactive protein. Area under the curve for receiver operating characteristics curve analysis of suPAR for 30-day mortality was 0.84 (95% CI 0.81 to 0.86). Furthermore, in the entire cohort, women had slightly higher suPAR compared with men, and suPAR was associated with age, admission time, admission to intensive care unit and Charlson score. Conclusions: In this large unselected population of acute medical patients, suPAR is strongly associated with disease severity, readmission and mortality after adjusting for all other risk factors, indicating that suPAR adds information to established prognostic indicators. While patients with low suPAR levels have low risk of readmission and mortality, patients with high suPAR levels have a high risk of adverse events.